AN IMPROVED CHROMATOGRAPHIC SEPARATION TECHNIQUE OF ND WITH APPLICATION TO NDO+ ISOTOPE ANALYSIS - Griselin M.; Van Belle J.C.; Pomiès C.; Vroon P.Z.; Van Soest M.C.; Davies G.R. (My University, 2001)
Isotopic analysis by Thermal Ionization Mass Spectrometry (TIMS) requires efficient chemical separation of the element of interest. This statement is particularly true for NdO+ measurements during which isobaric interferences must be minimized. Here, we present a new chromatographic procedure that efficiently separates Nd from other Light Rare-Earth Elements (LREE) and is ideal for NdO+ measurements. After separation of the LREE fraction from the bulk matrix, Nd is chemically separated using a High Pressure Liquid Chromatographic (HPLC) technique, with Aminex resin (Bio-Rad©) and a CH3OH–HAc–HNO3 eluent. This simple and low blank (10–15 pg) separation technique efficiently reduces isobaric interferences so that 140CeO+/144NdO+ and 141PrO+/144NdO+ ratios are generally below recommended values, ensuring no significant contribution from isobaric interferences.The NdO+ analytical technique also requires accurate determination of the oxygen isotope composition in TIMS since it is used to recalculate the Nd isotope composition of the samples. The results of a series of measurements performed to determine the oxygen isotope ratios (18O/16O=0.002040 and 17O/16O=0.000386) were used to constrain the parameters influencing the measurements. Loading technique and running conditions greatly affect measured oxygen isotope ratios. Guidelines to help accurately determine the oxygen isotope ratios are also presented. Combining the Aminex chromatographic separation with NdO+ measurements and accurately determined oxygen isotope ratios allows high precision measurements. A wide range of low abundance samples can be analyzed to a precision similar to that obtained on larger samples with conventional Nd+ technique (±0.000020, 2σ).